Army biometric applications : identifying and addressing sociocultural concerns - Woodward, John D., Jr (Rand, 2001)
Every human possesses virtually infallible forms of identification. Known as biometrics, examples include fingerprints. The US Army has undertaken an assessment of how it can use biometrics to improve security, efficiency and convenience. This report examines the sociocultural concerns that arise.